PHKA2 mutation spectrum in Korean patients with glycogen storage disease type IX: prevalence of deletion mutations. Issue 1 (December 2016) - Choi, Rihwa; Park, Hyung-Doo; Kang, Ben; Choi, So; Ki, Chang-Seok; Lee, Soo-Youn; Kim, Jong-Won; Song, Junghan; Choe, Yon Ho
Abstract Background Molecular diagnosis of glycogen storage diseases (GSDs) is important to enable accurate diagnoses and make appropriate therapeutic plans. The aim of this study was to evaluate thePHKA2 mutation spectrum in Korean patients with GSD type IX. Methods Thirteen Korean patients were tested forPHKA2 mutations using direct sequencing and a multiplex polymerase chain reaction method. A comprehensive review of the literature on previously reportedPHKA2 mutations in other ethnic populations was conducted for comparison. Results Among 13 patients tested, six unrelated male patients with GSD IX aged 2 to 6 years at the first diagnostic work-up for hepatomegaly with elevated aspartate transaminase (AST) and alanine transaminase (ALT) were found to havePHKA2 mutations. These patients had differentPHKA2 mutations: five were known mutations (c.537 + 5G > A, c.884G > A [p.Arg295His], c.3210_3212delGAG [p.Arg1072del], exon 8 deletion, and exons 27–33 deletion) and one was a novel mutation (exons 18–33 deletion). Notably, the most common type of mutation was gross deletion, in contrast to other ethnic populations in which the most common mutation type was sequence variant. Conclusions This study expands our knowledge of thePHKA2 mutation spectrum of GSD IX. Considering thePHKA2 mutation spectrum in Korean patients with GSD IX, molecular diagnostic methods for deletions should be conducted in conjunction with direct sequence analysis to enable accurate molecular diagnosis of this disease in the Korean population.